PERSEPSI PETANI TENTANG PENGARUH KINERJA PENYULUH TERHADAP KOMPETENSI PETANI PADI DI KABUPATEN ACEH BARAT (Rice Farmers Perceptions Of The Influence Of Extension Workers' Performance On The Competence Of Rice Farmers In West Aceh Regency) - HARAHAP, RAHMAT DILTA; WIRDA, BUNGA; FEBRIAN, AFRIZAL; KARYANTO, RIZAL (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
This study aims to assess how farmers perceive the impact of agricultural extension performance on rice farmers' ability in Alue Tampak Village, Kaway XVI Sub-district, West Aceh District. With a total population of 176 rice farmers, the study adopted a quantitative approach through a survey method. The sample was selected using the Slovin formula, resulting in 64 rice farmer respondents. Data were collected through questionnaires and analyzed using simple linear regression as well as hypothesis testing with the help of SPSS 20. The research findings indicated that farmers' perceptions of agricultural extension workers' performance positively affected their competence in rice farming. The R² value of 0.554 indicates that the performance of agricultural extension workers can explain 55.4% of the variation in farmers' competence, while factors beyond the scope of this study influence the remaining 44.6%. The regression test results yielded the equation Y = 2.599 + 0.631X + e, where the positive coefficient of 0.631 confirms the existence of a positive influence between agricultural extension performance and farmers' competencies.